Uma arquitetura para promover o uso de dispositivos com limitações computacionais na interação com mídias sintetizadas remotamente - Godoy, Arthur Pedro de (2014)
Computer graphics and virtual reality technologies allow audiovisual experiences with high level of realism, as the ones achieved in video games and movies. The synthetization of media with high degree of audiovisual realism demands specialized systems with high performance computing capacity. The profusion in the last decade of personal computing consumer electronics such as mobile and portable devices, encourages the interest in making possible, also in these devices, applications with high level of visual realism. However, due to the intrinsic limitations of the computing capability of mobile and portable devices, regarding to the physical characteristics of these devices, such as dimensions, electrical consume and heat dissipation, it s not possible directly process media with the same level of visual realism that is found in specialized systems. This research suggests the exploration of a traditional solution: the remote interaction with these applications. Challenges resulting from this approach are identified and studied. Solutions are proposed, analyzed and formalized in a architecture for reference. As a proof of concept the architecture is used in the development of applications on two scenarios: one in a local network with a media characterized by its low tolerance in delay of interaction response and another with a high tolerance media through the Internet. Also is showed the flexibility of the proposed architecture by integrating one of the applications developed with a multimedia context.